Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine

Highly selective C-N and C-S dual functionalization of 1,3-dicarbonyl derivatives using TBHP as an oxidant - Bagad, Pooja K.; Darole, Ratanamala S.; Krishna, G. Rama; Senthilkumar, Beeran (Journal of Organic Chemistry, 2024)
A direct electrosynthesis/photocatalyst-free, atom-economical, and efficient method for the selective synthesis of (E)-3-amino-2-thiocyanato-alpha,beta-unsaturated carbonyl compounds is described through a given protocol. The present approach features the use of inexpensive ammonium thiocyanate to achieve dual functionalization of 1,3-dicarbonyl compounds using TBHP as an oxidant, providing a rapid and practical route to the selective formation of both C-N and C-S bonds via a radical process. This method offers a broad substrate scope with excellent yield and allows for further exploration of the products to construct heterocyclic compounds and other functionalities.

Effectiveness of 3-amino-2-thiocyanato-α, β-unsaturated carbonyl compounds against chikungunya virus - Alagarasu, Kalichamy; Dhote, Radhika; Bagad, Pooja K.; Kharikar, Dwidhesh; Patil, Poonam; Roy, Diya; Shukla, Shridhar; Cherian, Sarah; Senthilkumar, Beeran; Parashar, Deepti (Future Medicinal Chemistry, 2025)
Aim Chikungunya fever (CHIKF) caused by the chikungunya virus (CHIKV) is characterized by the presence of long-term polyarthralgia in a minor proportion of the infected patients. Currently, there are no FDA-approved antivirals available. This study evaluated the anti-CHIKV potential of 16 synthetic 3-amino-2-thiocyanato-alpha, beta-unsaturated carbonyl compounds and elucidated their probable mechanisms of action. Methods Anti-CHIKV activity of 16 compounds were investigated in Vero CCL-81 cells using focus forming unit assay (FFU). Dose-dependent and time-dependent antiviral assays were performed for the effective compounds. Molecular docking was performed to find out their interactions with viral proteins. Results Five compounds showed promising anti-CHIKV activity by reducing viral titer with >1 log10 FFU/ml. Dose-dependent studies revealed that the compound 3 g was more effective in reducing the virus titer with a half-maximal inhibitory concentration (IC50) of 0.4315 mu M and a selectivity index of 35.99. Docking analyses revealed that all the compounds mainly interact with the non-structural proteins of CHIKV. Conclusions These findings demonstrate the in vitro anti-CHIKV activity of these compounds, and their possible mode of action via interference with early stages of infection and replication processes. This study warrants further preclinical and clinical evaluation to establish their safety and efficacy as novel anti-CHIKV therapeutics.
Keywords: 3-amino-2-thiocyanato-alpha; antivirals; beta-unsaturated carbonyl compounds; Chikungunya virus (CHIKV); nsP2 helicase; therapeutics